1997
DOI: 10.1128/jvi.71.6.4707-4716.1997
|View full text |Cite
|
Sign up to set email alerts
|

RevM10-expressing T cells derived in vivo from transduced human hematopoietic stem-progenitor cells inhibit human immunodeficiency virus replication

Abstract: A key feature of the pathogenesis of human immunodeficiency virus type 1 (HIV-1) infection is the gradual loss of CD4-positive T cells. A number of gene therapy strategies have been designed with the intent of inhibiting HIV replication in mature T cells. As T cells are products of hematolymphoid differentiation, insertion of antiviral genes into hematopoietic stem cells could serve as a vehicle to confer long-term protection in progeny T cells derived from transduced stem cells. One such "cellular immunizatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
17
0

Year Published

1997
1997
2020
2020

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 96 publications
(17 citation statements)
references
References 43 publications
0
17
0
Order By: Relevance
“…This conjoint organ provides a microenvironment for long‐term T‐lineage differentiation. Importantly, we and others have previously shown that direct injection of exogenous CD34+ human hematopoietic progenitor cells into Thy/Liv implants in sublethally irradiated SCID‐hu mice results in engraftment and T‐lymphoid differentiation of the exogenous cells [9, 19–21].…”
Section: Resultsmentioning
confidence: 99%
“…This conjoint organ provides a microenvironment for long‐term T‐lineage differentiation. Importantly, we and others have previously shown that direct injection of exogenous CD34+ human hematopoietic progenitor cells into Thy/Liv implants in sublethally irradiated SCID‐hu mice results in engraftment and T‐lymphoid differentiation of the exogenous cells [9, 19–21].…”
Section: Resultsmentioning
confidence: 99%
“…When expressed in transfected cells, this mutant Rev protein successfully inhibited the function of its wild-type counterpart. That RevM10 serves as an effective trans-dominant inhibitor of Rev function was further validated by others [40][41][42][43][44] thereby catapulting RevM10-based gene therapy into Phase I and II clinical trials [45]. However, a subsequent study by Hamm et al [46], involving passage of HIV-1 in a T-cell line constitutively expressing RevM10, reported rapid emergence of a RevM10-resistant virus [46].…”
Section: Resistance To Trans-dominant Revm10 Therapy Induces a Conformentioning
confidence: 99%
“…The antiviral effect of VprIE was also compared to that obtained with RevM10, a trans-dominant mutant form of HIV-1 Rev that has been shown to delay HIV-1 replication in transduced cell lines, primary T cells, and CD34-enriched hematopoietic progenitor stem cells (2,4,27). Jurkat cells were transduced with pBabepuro-RevM10, and the resulting puromycin-resistant population, Jurkat-RevM10 cells, was infected with 100,000 cpm of HxBRU or HxBRU-R-.…”
Section: Protein Expression and Replication Potential Of Hiv-1 Virionmentioning
confidence: 99%